2019
DOI: 10.1080/09603123.2019.1691719
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater, soil and compost, as possible sources of virulent and antibiotic-resistant Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a major public health concern all around the world. In the frame of this work, a set of diverse environmental P. aeruginosa isolates with various antibiotic resistance profiles were examined in a Galleria mellonella virulence model. Motility, serotypes, virulence factors and biofilm-forming ability were also examined. Molecular types were determined by pulsed-field gel electrophoresis (PFGE). Based on our results, the majority of environmental isolates were virulent in the G. mellonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 64 publications
(68 reference statements)
0
22
1
Order By: Relevance
“…To this end, we screened three environmental sources where P. aeruginosa is commonly present: sewage, soil, and river [ 30 , 31 ]. We isolated 18 Pseudomonas phages from these environments in different cities, Rasht and Hamadan, in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we screened three environmental sources where P. aeruginosa is commonly present: sewage, soil, and river [ 30 , 31 ]. We isolated 18 Pseudomonas phages from these environments in different cities, Rasht and Hamadan, in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the nosocomial source, industrial wastewater effluents, hydrocarbon-contaminated sites, and composts are also suggested as overlooked hot spots for P. aeruginosa. , …”
Section: Resultsmentioning
confidence: 99%
“…A study group in Hungary has published the occurrence of MDR P. aeruginosa found in environmental sites contaminated by hydrocarbons between the period of 2002-2007; carbapenem-resistance was noted in 33% of isolates (Kaszab et al 2010). The same study group has also recently reported ceftriaxone and imipenem resistance in 25.0% of tested environmental P. aeruginosa isolates; in addition, five out of the 44 isolates originating from sources as groundwater, soil or compost showed close genetic relatedness to clinically relevant pulse-field types based on pulse-field gel electrophoresis (PFGE) (Kaszab et al 2019). In a laboratory-based study, n = 250 carbapenem-resistant P. aeruginosa were surveyed for their susceptibilities against ceftazidime-avibactam (C/A) and ceftolozane-tazobactam (C/T), in addition to a phenotypic-genotypic study for carbapenemaseproduction: prevalence of resistance to C/A and C/T was 33.6% and 32.4%, respectively; isolates producing positive CIM-tests were VIM (80%) or NDM (11%) producers (O'Neall et al 2020).…”
Section: Gajdács Et Almentioning
confidence: 90%